Inquiry in Action: Reflections on the Implementation of Best Practices in Child- and Family-Focused University–Community Partnerships. Issue 1 (January 2021) - Walsh, Mary E.; Adams, Shauna M.; Ferguson, Susan; Hearst, Mary O.; Jones, Jo-Viviane; Wall, Shavaun; Petsagourakis, Despina; Chung, Agnes; Shannon, Una; Theodorakakis, Maria
University–community partnerships (UCPs) are increasingly utilized to address issues in education. In this article, we present reflections on best practices for child- and family-focused UCPs. These reflections emerged before, during, and after a convening that brought together representatives from five UCPs in the United States that emphasized early childhood development and received funding from the same philanthropic source. The convening elicited perspectives on best practices for UCPs and identified community- and university-related contextual factors that affected implementation of these best practices. The findings from this study will contribute to the enhancement of future UCPs in education.